Reframing Higher Education Value: A Systematic Literature Review on Gen Z’s Perception in the Digital Economy Era - Marlina, Lina (Indonesian Scientific Publication, 2025)
Generation Z has grown up in a hyperconnected world where digital careers often deliver faster and more visible success than traditional academic routes. While numerous studies have addressed digital literacy, career motivation, or higher education individually, little is known about how these factors intersect to shape Gen Z’s perception of higher education’s value in the digital economy. This lack of integrated understanding limits universities’ and policymakers’ ability to respond effectively to Gen Z’s evolving career expectations. This study addresses the gap by examining how Gen Z evaluates the relevance of higher education when success is increasingly defined by self-directed learning, digital visibility, and entrepreneurial opportunities. A systematic literature review was conducted using ScienceDirect, applying Boolean-based queries on Generation Z, higher education, perception, motivation, and digital careers. From an initial pool of 3,255 records, 63 research articles (2016–2025) met the inclusion criteria based on publication year, article type, subject relevance, language, and access status. Thematic synthesis identified five key influences: personal motivation, the appeal of alternative careers, perceived relevance of higher education, institutional responsiveness, and socioeconomic pressure. These findings contribute to a conceptual framework that repositions higher education within the realities of the digital economy, offering strategic insights for universities and policymakers to design more adaptive, relevant, and attractive learning pathways for the next generation.